Menggagas Pertanian Berkelanjutan Melalui Akuaponik: Penerapan dan Dampaknya dalam Pengabdian kepada Masyarakat Kalirungkut - Hilman Hasibur Rohman; Eliada Samuel Pasaribu; Praja Firdaus Nuryananda; Risqi Firdaus Setiawan (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
Kalirungkut Village is one of the urban areas located in Rungkut Sub-district, Surabaya. The area of Kelurahan Kalirungkut is 2.58 km2, divided into 15 RWs (neighborhood units) and 86 RTs (community units) (Statistics Indonesia, Surabaya 2016). The population of this neighborhood is approximately 22,949 people, consisting of 11,345 males and 11,604 females (Kalirungkut Village, 2022). Within the neighborhood, there are 11 active industrial companies, including 7 large-scale industries and 4 small-scale industries (Statistics Indonesia, Surabaya 2019). The significant population and industrial activities in the area require a large amount of land, resulting in a reduction of agricultural land. Therefore, the objective of the community service activity is to create a sustainable farming strategy through the design and implementation of aquaponics. The community service method consists of three stages: survey and preparation, implementation of activities, and maintenance and monitoring of results. The outcome of the community service activity is the establishment of an aquaponics farming system located in the yard of one of the residents in Kalirungkut, namely Mrs. Ismudji Rahayuningsih.